2016
DOI: 10.1007/s00467-016-3481-7
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and low-grade inflammation in pediatric kidney transplant recipients

Abstract: Anemia, but not elevated inflammatory indices, was associated with poor concomitant and subsequent graft function during a 10-year follow-up in pediatric RTx patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Most of the RTx recipients (79%) enrolled in our study underwent transplantation more than a year ago; thus this study mainly focused on “late” PTA. We found that the prevalence of anemia in the RTx group was 46% and similar to previous studies on PTA indicating the prevalence ranging between 22% and 82% in pediatric patients 7‐12 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most of the RTx recipients (79%) enrolled in our study underwent transplantation more than a year ago; thus this study mainly focused on “late” PTA. We found that the prevalence of anemia in the RTx group was 46% and similar to previous studies on PTA indicating the prevalence ranging between 22% and 82% in pediatric patients 7‐12 …”
Section: Discussionsupporting
confidence: 89%
“…We found that the prevalence of anemia in the RTx group was 46% and similar to previous studies on PTA indicating the prevalence ranging between 22% and 82% in pediatric patients. [7][8][9][10][11][12] In the RTx group, Hb concentration was positively correlated with eGFR. Moreover, anemic patients had lower levels of eGFR than non-anemic individuals.…”
Section: Ta B L Ementioning
confidence: 93%
See 2 more Smart Citations
“…In pediatric kidney transplant recipients, anemia is common [1][2][3][4][5][6] and associated with worse allograft function [5,6]. The etiology of post-transplant anemia is oftentimes complex and multifactorial.…”
Section: Introductionmentioning
confidence: 99%